Pulmonary function test in formalin exposed and nonexposed subjects: A comparative study - P Uthiravelu; A Saravanan; C Kishor Kumar; V Vaithiyanandane (Wolters Kluwer Medknow Publications, 2015)
Background: The main function of the lung is gas exchange, which can be assessed in several ways. A spirometer measures the flow and the volumes of the inspired and expired air. The thoracic and abdominal muscle strength plays an important role in pulmonary function and diffusing lung capacity. Aims and Objectives: The aim of this study was to assess the effects of formalin exposure on the pulmonary function to compare with healthy individuals. To assess the chronic effects of formalin exposure on Pulmonary function tests (PFTs) in the faculties, lab technicians and attender of the Department of Anatomy and Pathology of SRM Medical Hospital and Research Centre, Kattankulathur. Materials and Methods: This prospective study was carried out in 50 healthy formalin exposed subjects (at least 5 years exposure) from Department of Anatomy and Pathology of SRM Medical College Hospital and Research Centre, Kattankulathur and 50 healthy controls of same age group of this study were included after obtaining ethical clearance and consent 'Easy One Pro Spirometer (Ndd Medical Technologies, Cheshire SK 101LT, United Kingdom) was used to find out the PFT. Results: Student's t-test was applied to compare the PFT parameters between formalin exposed and formalin nonexposed group. There was a significant difference in mean and standard deviation of pulmonary parameters with the P < 0.005 in formalin exposed, which shows that they have lesser ventilatory drive. Conclusion: The formalin exposed subjects in our study presented with a mixed disorder of both obstructive and restrictive type. We also found that there was a negative correlation of pulmonary function with that of the degree and duration of exposure to formalin.